Pemanfaatan Media Interaktif Berbasis Augmented Reality dalam Pembelajaran Topik Klasifikasi Hewan Berdasarkan Makanan - Tasya’ah Tasya’ah; Risyda Dzul Fadlilah; Marsanda Dwi Khanifah; Muhammad Nofan Zulfahmi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Education is the main foundation for the progress of society and individuals, Basic education is very important to build students' knowledge and skills, especially in the field of science. Conventional methods, such as the use of illustrations and textbooks, are often not interesting and interactive. Digital technology presents new opportunities in learning innovation, including by utilizing augmented reality (AR). This study aims to analyze and evaluate the use of interactive media based on augmented reality (AR) in learning the topic of animal classification based on their type of food. The method used is a literature study by reviewing various scientific sources, including journals, articles, and relevant research reports in the last five years. AR-based interactive media offers an innovative and immersive learning experience, allowing students to interact directly with virtual objects in the form of three-dimensional (3D) visualizations. The results of the study show that the use of AR can improve students' understanding of the material, increase engagement in learning, and provide a more interesting and contextual learning experience. In addition, AR media is considered effective in helping students identify animal characteristics based on eating habits, such as herbivores, carnivores, and omnivores. This study concludes that the integration of AR in science learning at the elementary school level has great potential to improve learning effectiveness.